(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Semantic features of pedagogical terms are generally described at two levels of complexity:• Primary structure: implementing pedagogical terms as other words using their secondary meaning.• Secondary structure: the linear arrangement of terms devoted to pedagogical spere and their dominant meaning